The Ultimate MacAddict Holiday Gadgets Guide. - Lu, Cathy
We dug up the absolute coolest gifts (both Mac and PC) for the music lover, videographer, road warrior, and Mac addict in your life. They're so cool, you'll want to keep them for yourself.